Bone Cells Differentiation: How CFTR Mutations May Rule the Game of Stem Cells Commitment? - Dumortier, Claire; Danopoulos, Soula; Velard, Frédéric; Al Alam, Denise (Frontiers in Cell and Developmental Biology, 2021)
Cystic fibrosis-related bone disease has emerged as a significant comorbidity of CF and is characterized by decreased bone formation and increased bone resorption. Both osteoblast and osteoclast differentiations are impacted by CFTR mutations. The defect of CFTR chloride channel or the loss of CFTR’s ability to interact with other proteins affect several signalling pathways involved in stem cell differentiation and the commitment of these cells toward bone lineages. Specifically, TGF-β, NF-КB, PI3K/AKT and MAPK/ERK signalling are disturbed by CFTR mutations, thus perturbing stem cell differentiation. High inflammation in patients changes myeloid lineage secretion, affecting both myeloid and mesenchymal differentiation. In osteoblast, Wnt signalling is impacted, resulting in consequences for both bone formation and resorption. Finally, CFTR could also have a direct role in osteoclast’s resorptive function. In this review, we summarize the existing literature on the role of CFTR mutations on the commitment of induced pluripotent stem cells to bone cells.